Biosafety, Antioxidant and Antidiarrhoeal Potentials of Afzelia africana Seed n-Hexane Extract - G. I. Ndukwe; J. O. Okhiku; F. G. Obomanu; G. O. Benjamin (Journal of Applied Sciences and Environmental Management, 2022)
This study evaluated the biosafety, phytochemicals, antioxidant activity, acute toxicological profile and antidiarrhoeal property of n-hexane extract of Afzelia africana seeds. Results from the phytochemical profiling (using gas chromatography - mass spectrometry technique) elicited the presence of hexadecanoic acid (34.97 %), 9, 12, 15-octadecatrien-1-ol (16.27%) and oleic acid (6.71%) as major compounds associated with antioxidant and antidiarrhoeal effects. The study revealed that A. africana seed possesses antioxidant potentials across four models at 100 ?g/ml (39.6%, 59.6%, 48.11% and 0.765 for 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging, ferrous ion chelating, hydrogen peroxide scavenging, and reducing power assays respectively). No adverse effect or lethality was recorded at ≤5000 mg of extract per kg body weight of tested animals after 14 days observation. In castor oil induced diarrhoea, a significant (p<0.05) increase in delayed onset of stooling and percentage inhibition (up to 92.4%) with decrease in defecation frequency were observed across the treated groups when compared with the control. Similarly, the extract showed a significant (p<0.05) dose dependent decrease in gastrointestinal motility with increase in percentage inhibition (up to 91.9%) in charcoal meal test. In conclusion, Afzelia africana seed antidiarrhoeal property has been validated and its folklore benefit affirmed by this study.